Berlusconi on trial: some lessons for judicial accountability. - Guarnieri, C (2011)
The policy brief shows how the wide powers afforded public prosecutors and the high rate of prosecutions of politicians in Italy has embroiled the judiciary in political controversies and has the effect of calling into question their impartiality, a fact clearly encouraged by Berlusconi and his supporters.